An industrial arts complex - Manianglung, Rocky D. (Manila : National University, 2000)
In this study, the designer does not just focus in utilizing the interrelated branches of industrial arts, but also - for this is supposedly, a complex on showcasing what creativity, productivity, willingness and eagerness to learn and aspiration would sum up together - is "finish product."
Keywords: INDUSTRIAL ARTS